Predicting the likelihood and intensity of mosquito infection from sex specific Plasmodium falciparum gametocyte density - John Bradley; Will Stone; Dari F Da; Isabelle Morlais; Alassane Dicko; Anna Cohuet; Wamdaogo M Guelbeogo; Almahamoudou Mahamar; Sandrine Nsango; Harouna M Soumaré; Halimatou Diawara; Kjerstin Lanke; et al. (eLife, 2018)
Understanding the importance of gametocyte density on human-to-mosquito transmission is of immediate relevance to malaria control. Previous work (Churcher et al., 2013) indicated a complex relationship between gametocyte density and mosquito infection. Here we use data from 148 feeding experiments on naturally infected gametocyte carriers to show that the relationship is much simpler and depends on both female and male parasite density. The proportion of mosquitoes infected is primarily determined by the density of female gametocytes though transmission from low gametocyte densities may be impeded by a lack of male parasites. Improved precision of gametocyte quantification simplifies the shape of the relationship with infection increasing rapidly before plateauing at higher densities. The mean number of oocysts per mosquito rises quickly with gametocyte density but continues to increase across densities examined. The work highlights the importance of measuring both female and male gametocyte density when estimating the human reservoir of infection.